(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The COVID-19 pandemic forced an unprecedented, rapid shift to emergency remote teaching that transformed teachers’ roles, amplified their workloads, and introduced new sources of stress tied to technology use. This article examines digital teaching workload and tech-induced stress (commonly called “technostress”) among school staff in the Delhi region in the post-COVID period. Drawing on theoretical frameworks of burnout and job demands–resources, international and Indian empirical studies, government and sector reports, and post-pandemic literature on hybrid/blended modes, the paper maps how pandemic-era digitalization produced persistent changes in time use, administrative duties, and emotional labour for educators. We document mechanisms through which digital workload generates stress—continuous availability, instructional redesign, platform learning, information overload, and work–home boundary erosion—and show how these translate into emotional exhaustion, reduced job satisfaction, and intentions to leave. The article offers policy and school-level recommendations (workload auditing, protected planning time, structured tech training, mental-health supports, and contractual reforms) and points to future research priorities including longitudinal monitoring, intervention trials, and focused studies on contractual/para-teachers in Delhi’s heterogeneous school ecosystem. Key implications underscore the need to treat tech-induced stress as an organizational and policy problem, not solely an individual deficiency.